Childhood Maltreatment and Spiritual Well-Being: Intolerance of Uncertainty and Emotion Regulation as Mediators in Turkish Sample - Yilmaz, Fatma Betul; Satici, Seydi Ahmet (SPRINGER, 2024)
Spiritual well-being is a phenomenon that enhances the quality of life and acts as a protective factor against stress and negative emotions. The purpose of this study was to investigate whether childhood psychological maltreatment is related to spiritual well-being and whether intolerance of uncertainty and emotion regulation serially mediate this relationship. The study sample comprised 330 participants aged between 18 and 55 years from 46 out of the 81 cities in Turkiye. The study participants completed the Psychological Maltreatment Questionnaire, Intolerance of Uncertainty Scale, Emotion Regulation Scale, and Spiritual Well-Being Scale, a scale derived from the Functional Assessment of Chronic Illness Therapy-Spiritual Well-Being that measures spiritual well-being by using the conceptualization of meaning and peace. The data obtained were analyzed using a two-step structural equation modeling approach, which indicated that childhood psychological maltreatment has an association with spiritual well-being, and this relationship is mediated by both intolerance of uncertainty and emotion regulation. The findings are discussed in the context of the literature on spiritual well-being.
Keywords: Spiritual well-being; Childhood psychological maltreatment; Intolerance of uncertainty; Emotion regulation; QUALITY-OF-LIFE; MENTAL-HEALTH; ANXIETY; ABUSE; MODEL; ADJUSTMENT; CHILDREN; IMPACT; DETERMINANTS; DIFFICULTIES; Public, Environmental & Occupational Health; Religion